(3QSGdI GdTgjO GdKGfjs - (3GdYGedj GdLYHj, GdTgjO GdKGfj, Rjf GdOjf Hf Ydj Hf CMeO, (B966 (3g`s
(3ChdgG (B:s
(3HYO MeO Gddg Ydi fYeg GdYXGe (B...(3agPg LedI ef GdcdGe aj JMbjb eSCdI abgjI TgjQI aj GdaJhi YGeI aj GdHdhi jYed HLhGHgG GdeJabg GdbGUQ hjYLR Yf cTa MLGHgG Gdabjg GdeGgQ hCfG CQLh HeG QbeJg aj gPg GdChQGb (B...s
(3BNQgG (B:s
... (3hEf cGf Mceg GdJeGe GTJQW chf eG HYO Pdc eSGaI hdG jVe Edi eG SHb ef GdSjQ dCfg NGQL Yf Mce GdeSGaQ dGfJXGQg agh aj bhI bGUO eG Ohf GdeSGaI hbO JbOe JaUjdg(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\ 64s
(3GdPQjYI (B17\553s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis